2004
DOI: 10.1016/s0168-6496(03)00281-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability and diversity of water column prokaryotic communities in the eastern North Atlantic

Abstract: This work describes the microbial community structure in the water column at the Porcupine Abyssal Plain in the eastern North Atlantic. Restriction fragment length polymorphism analysis was carried out on clone libraries constructed from samples collected at 100 m, 1000 m, 3000 m, 10 m above bottom and sediment contact water during July 1997 and March 1998. Simpson (1/D) and Shannon (H') diversity indices revealed temporal and spatial variations in the community structure and complexity. Higher diversity was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…The Deltaproteobacteria were dominated by the SAR324 cluster , another typical deep water cluster earlier reported from the Arctic (Bano and Hollibaugh, 2002) but also from the Antarctic (Lopez-Garcia et al, 2001) and North Atlantic (Gonzalez et al, 2000). The SAR406 cluster, previously detected in various oceanic provinces (Gordon and Giovannoni, 1996;Gallagher et al, 2004;Pham et al, 2008), as well as the Chloroflexi SAR202 cluster , described as abundant and ubiquitous in meso-and bathypelagic waters Bano and Hollibaugh, 2002;Morris et al, 2004;Varela et al, 2008a), were other abundant clusters of the dark ocean.…”
Section: Discussionsupporting
confidence: 51%
“…The Deltaproteobacteria were dominated by the SAR324 cluster , another typical deep water cluster earlier reported from the Arctic (Bano and Hollibaugh, 2002) but also from the Antarctic (Lopez-Garcia et al, 2001) and North Atlantic (Gonzalez et al, 2000). The SAR406 cluster, previously detected in various oceanic provinces (Gordon and Giovannoni, 1996;Gallagher et al, 2004;Pham et al, 2008), as well as the Chloroflexi SAR202 cluster , described as abundant and ubiquitous in meso-and bathypelagic waters Bano and Hollibaugh, 2002;Morris et al, 2004;Varela et al, 2008a), were other abundant clusters of the dark ocean.…”
Section: Discussionsupporting
confidence: 51%
“…Previous reports have described seasonal variation in bacterial community structure in estuarine seawater, but have discussed the variation in relation to primary productivity or nutrient supply 13,15,20,27) . The CCA analysis undertaken for this study indicated that water temperature is a major environmental factor associated with the seasonal variation in community structure, but POC and nitrite plus nitrate concentrations were associated with vertical variation in the stratified season (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This pelagic archaeal clade has been identified from surface waters of different marine areas and seems to be dominant here. Furthermore, MG-II members have been also found associated with tropical corals (Massana et al, 1997(Massana et al, , 2000Delong et al, 1999;Gallagher et al, 2004) and blooms have been observed in surface water of Monterey Bay and of the North Sea during summer (Pernthaler et al, 2002;Delong, 2003). Sequences of uncultured Archaea have been originally classified according to their geographic location.…”
Section: Archaeal Diversitymentioning
confidence: 99%